Ergonomic Checkpoints : Practical and easy-to-implement solutions for improving safety, health and working conditions. - Office, International Labor (International Labour Office, 2010)
Fully revised and expanded, this new edition of the highly successful Ergonomic checkpoints is aimed at reducing work-related accidents and diseases and improving safety, health and working conditions. Building on the wealth of experience of practitioners in applying these checkpoints, the second edition features revised text, additional checkpoints and new, full-colour illustrations.